2013
DOI: 10.1186/1471-2369-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic asymptomatic pyuria precedes overt urinary tract infection and deterioration of renal function in autosomal dominant polycystic kidney disease

Abstract: BackgroundUrinary tract infection (UTI) occurs in 30%-50% of individuals with autosomal dominant polycystic kidney disease (ADPKD). However, the clinical relevance of asymptomatic pyuria in ADPKD patients remains unknown.MethodsWe retrospectively reviewed medical records of 256 ADPKD patients who registered to the ADPKD clinic at Seoul National University Hospital from Aug 1999 to Aug 2010. We defined the asymptomatic pyuria as more than 5-9 white blood cells in high-power field with no related symptoms or sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 29 publications
4
69
0
Order By: Relevance
“…However, several comorbidities such as cancer, arthritis, and chronic kidney disease were higher than normative values. This is expected, as each of these chronic conditions is associated with an increased risk of frailty (4749). Because physical activity and diet quality were measured only once at baseline, it is unknown if increasing physical activity or improving diet quality would improve distal health outcomes among prefrail and frail older adults.…”
Section: Discussionmentioning
confidence: 95%
“…However, several comorbidities such as cancer, arthritis, and chronic kidney disease were higher than normative values. This is expected, as each of these chronic conditions is associated with an increased risk of frailty (4749). Because physical activity and diet quality were measured only once at baseline, it is unknown if increasing physical activity or improving diet quality would improve distal health outcomes among prefrail and frail older adults.…”
Section: Discussionmentioning
confidence: 95%
“…38 A third retrospective, singlecenter study suggested that asymptomatic pyuria and particularly, overt UTI were associated with faster decline in renal function, but it is unclear whether this result was independent of other factors, such as baseline GFR and TKV. 39 In addition, overt UTI was uncommon in that study, occurring in only 33 of 256 patients during a mean observation period of 81 months. It remains, therefore, uncertain whether UTIs play a significant role in the loss of renal function in ADPKD.…”
Section: Multiple Urinary Tract Infectionsmentioning
confidence: 99%
“…The typical concentration levels of TNF-α in human urine samples are often below the DLs of conventional cytokine detection platforms. 41 Those of IL-8, on the other hand, typically exhibit values above several tens of pg/mL and well into the ng/mL range, 42,43 which can be determined with traditional techniques. Therefore, we carried out both ELISA- and ZnO NRs-based assays from the same set of patient samples.…”
Section: Resultsmentioning
confidence: 99%